2014
DOI: 10.1136/jnnp-2014-309436
|View full text |Cite
|
Sign up to set email alerts
|

Impaired imitation of gestures in mild dementia: comparison of dementia with Lewy bodies, Alzheimer's disease and vascular dementia

Abstract: Our study revealed that imitation of bimanual gestures was impaired non-specifically in about half of the patients with mild dementia, whereas imitation of finger gestures was significantly more impaired in patients with early DLB than in those with AD or SVaD. Although the sensitivity was not high, the imitation tasks may provide additional information for diagnosis of mild dementia, especially for DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 21 publications
3
35
1
Order By: Relevance
“…It has even been suggested that a reduced number of angles on the Mini Mental State Examination (MMSE) pentagon copy could be a marker of prodromal DLB, with a specificity of 91% in discrimination from AD [53]. However, DLB is also associated with visuoperceptual deficits (see [54] for a review) and praxic difficulties [55]. Hence, it has been suggested that copying impairments in patients with DLB might be linked to combined praxis and visuoperceptual disturbances [56] instead of reflecting pure visuoconstructive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been suggested that a reduced number of angles on the Mini Mental State Examination (MMSE) pentagon copy could be a marker of prodromal DLB, with a specificity of 91% in discrimination from AD [53]. However, DLB is also associated with visuoperceptual deficits (see [54] for a review) and praxic difficulties [55]. Hence, it has been suggested that copying impairments in patients with DLB might be linked to combined praxis and visuoperceptual disturbances [56] instead of reflecting pure visuoconstructive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This impairment is often inversely proportional to subcortical cerebral injury, thus allowing clinicians to provide a more accurate prognosis for cognitive decline and functional impairment. [8][9][10][11][12] In 1920, Lipeman studied 84 patients who suffered strokes and discovered that, in addition to aphasia, the patients also had impairments of motor skills such as debilitated copying and imitative gestures. 13 Moreover, regarding more precise aspects of the diagnosis, CAMCOG has contributed towards evaluation of total praxis and its subitems through showing the relevance of some studies that have indicated that impairment of praxis abilities confirms that there is a risk of rapid evolution to severe cases of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Age-related decline specifically impacts timing processing and control of attentional load, which are viewed as primary factors in task performance of interlimb coordination in the upper extremity ( Krampe et al, 2010 ). In addition, cognitive impairment influences coordination, such that decreased imitation ability of bimanual gestures has been observed in older adults in the early stages of dementia ( Nagahama et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%